Inclusion of dietary Ulva ohnoi 5% modulates Solea senegalensis immune response during Photobacterium damselae subsp. piscicida infection. Issue 100 (May 2020) - Fumanal, Milena; Di Zeo, Daniel E.; Anguís, Victoria; Fernández-Diaz, Catalina; Alarcón, F. Javier; Piñera, Rocío; Albaladejo-Riad, Nora; Esteban, M. Angeles; Moriñigo, Miguel A.; Balebona, M. Carmen
Abstract: Macroalgae represent valuable sources of functional ingredients for fish diets, and the influence of supplemented aquafeeds on growth performance has been studied for some fish and seaweed species. In the present work, the potential immunomodulation exerted by U. ohnoi (5%) as dietary ingredient was investigated in Senegalese sole. After feeding with the experimental diets for 90 d, fish immune response before and after challenge with Photobacterium damselae subsp. piscicida ( Phdp ) was assessed. In absence of infection, systemic immune response was not modified by 5% U. ohnoi dietary inclusion for 90 d. Thus, no differences in liver and head kidney immune gene transcription or serum lysozyme, peroxidase, antiprotease and complement activities were observed based on the diet received by Senegalese sole specimens. Regarding mucosal immune parameters, no changes in gene transcription were detected in the skin and gills, whilst only tnf, cd4 and cd8 were significantly up-regulated in the intestine of fish fed with U. ohnoi, compared to the values obtained with control diet. On the contrary, when S. senegalensis specimens were challenged with Phdp, modulation of the immune response consisting in increased transcription of genes encoding complement ( c1q4, c3, c9 ), lysozyme g ( lysg ), tumor necrosis factor alpha ( tnfα ) as well as those involved in the antioxidant response ( gpx, sodmn ) and iron metabolism ( ferrm, hamp- 1) was observed in the liver of fish fed with U. ohnoi . In parallel, decreased inflammatory cytokine and complement encoding gene transcription was displayed by the spleen of fish receiving the algal diet. Though mortality rates due to Phdp challenge were not affected by the diet received, lower pathogen loads were detected in the liver of soles receiving U. ohnoi diet. Further research to investigate the effects of higher inclusion levels of this seaweed in fish diets, feeding during short periods as wells as to assess the response against other pathogens needs to be carried out. Highlights: Solea senegalensis was fed low inclusion level Ulva ohnoi (5%) for 90 days. Dietary U. ohnoi modulates S. senegalensis immune response during Phdp infection. Lower presence of Phdp is detected in the liver of S. senegalensis fed U. ohnoi .